Comparative Analysis of Phraseological Units with Component-Zoonym - Y. N. Kulichenko; E. M. Korolevskaya (Научный диалог, 2017)
The article is devoted to comparative research in Russian, English and Italian phraseological units with the component-zoonym. The relevance of the study is determined by the importance of the analysed units to understand the peculiarities of mentality of representatives of different linguistic cultures and improving intercultural communication, since these idioms demonstrate the commonality and difference in values, stereotypes and behaviour patterns in national cultures. This article gives a review of the scientific literature devoted to the study of zoonyms and presents results of own research. Its novelty is seen in the fact that a detailed classification of phraseological units with the component-zoonym is proposed on the basis of the analysis of their structural and semantic peculiarities on the material of three non-closely related languages. According to the structure there are substantive, adjectival, verbal and adverbial idioms. Within the structural groups according to the semantics there are subgroups used to describe a person, his experience, status, positive and negative qualities, typical properties, emotional and physical condition, behaviour, speech, interpersonal relations etc. The attention is paid to evaluative connotations of the considered units. The dominant images in phraseology of Russian, English and Italian languages are identified and their meanings are examined in the comparative aspect.